Determinants of SMEs' Adoption of Sharia Bank Products - Fauzi, Muchamad Rizky; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT Aksara Indo Rajawali, 2024)
This study investigates the influence of promotion on Islamic Bank product adoption among SMEs in the Kediri Residency region, employing a quantitative approach with data collected through questionnaires distributed to registered SME actors. The research reveals that while promotion does not directly positively impact product adoption decisions, it indirectly enhances Islamic Banks' image and customer trust, thereby increasing the likelihood of product adoption. By demonstrating the complex relationship between promotional strategies and SME decision-making, the study highlights the importance of comprehensive marketing approaches that focus on building institutional credibility and trust, rather than relying solely on traditional promotional techniques. The findings offer valuable insights for Islamic Banks seeking to expand their market presence and effectively engage with SME stakeholders in an increasingly competitive financial landscape.